Individual Variation in the Late Positive Complex to Semantic Anomalies - Kos, Miriam; Van den Brink, Danielle; Hagoort, Peter (Frontiers in Psychology, 2012)
It is well-known that, within ERP paradigms of sentence processing, semantically anomalous words elicit N400 effects. Less clear, however, is what happens after the N400. In some cases N400 effects are followed by Late Positive Complexes (LPC), whereas in other cases such effects are lacking. We investigated several factors which could affect the LPC, such as contextual constraint, inter-individual variation and working memory. Seventy-two participants read sentences containing a semantic manipulation (Whipped cream tastes sweet/anxious and creamy). Neither contextual constraint nor working memory correlated with the LPC. Inter-individual variation played a substantial role in the elicitation of the LPC with about half of the participants showing a negative response and the other half showing an LPC. This individual variation correlated with a syntactic ERP as well as an alternative semantic manipulation. In conclusion, our results show that inter-individual variation plays a large role in the elicitation of the LPC and this may account for the diversity in LPC findings in language research.